Cocoa Seed Shelf-Life and Seed Germination as Influenced by Pectin-Coat Application - Rosyidatul Putri Munawaroh; Indah Anita-Sari; Sri Rahayu (Indonesian Coffee and Cocoa Research Institute, 2020)
The time difference between the availability and the needs of cocoa seeds causes the national needs can not be fulfilled. Recalcitrant cocoa seed cannot be stored for a long time, germinating seeds during the storage process change in abnormal seedling growth. One of seed technology to maintain the seed quality during the storage is seed coating. Pectin is one of the compounds that can be used for coating on several commodities, also possible to be used on cocoa seeds. The study was conducted at Plant Breeding Laboratory of Indonesian Coffee and Cocoa Research Institute, Jember. The experiment used a factorial randomized completely block design consisting of two factors. The first factor were concentration of pectin 0% (control), 1%, and 3%, while the second factor were shelflife of 1 week, 2 weeks, and 3 weeks. Each treatment combination was repeatedthree times. The results showed that pectin-coat treatment could keep cocoa seeds from germinating for 3 weeks but unable to maintain the quality of seeds during storage.